Where are the gaps in education in the field of rare lung disease?: perspectives from the ERN-LUNG educational programme survey - Powell, Pippa; Kreuter, Michael; Wijsenbeek-Lourens, Marlies (Breathe, 2019)
Tweetable abstract ERSpublications - click to tweetIt is vital that education in the field of rare lung rare disease is made a priority for healthcare givers as well as for patients http://ow.ly/ysPs30o9v6b